2003
DOI: 10.1046/j.1365-2958.2003.t01-1-03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ordination of pathogenicity island expression by the BipA GTPase in enteropathogenic Escherichia coli (EPEC)

Abstract: SummaryBipA is a novel member of the ribosome binding GTPase superfamily and is widely distributed in bacteria and plants. We report here that it regulates multiple cell surface-and virulence-associated components in the enteropathogenic Escherichia coli (EPEC) strain E2348/69. The regulated components include bacterial flagella, the espC pathogenicity island and a type III secretion system specified by the locus of enterocyte effacement (LEE). BipA positively regulated the espC and LEE gene clusters through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 53 publications
3
80
0
3
Order By: Relevance
“…Therefore, this is not a general effect on all promoters arising from the ability of Fis to influence DNA topology. Our discovery that Fis regulates the expression of all three type III secretion systems in Salmonella is in keeping with other studies that have pointed to regulatory overlaps between virulence genes and flagella in Salmonella (Eichelberg & Galan, 2000;Ellermeier & Slauch, 2003;Lawhon et al, 2003) and other bacteria (Goodier & Ahmer, 2001;Grant et al, 2003). The effect of Fis on murein lipoprotein expression is also relevant here, since the lpp gene product is a structural component of the cell envelope.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, this is not a general effect on all promoters arising from the ability of Fis to influence DNA topology. Our discovery that Fis regulates the expression of all three type III secretion systems in Salmonella is in keeping with other studies that have pointed to regulatory overlaps between virulence genes and flagella in Salmonella (Eichelberg & Galan, 2000;Ellermeier & Slauch, 2003;Lawhon et al, 2003) and other bacteria (Goodier & Ahmer, 2001;Grant et al, 2003). The effect of Fis on murein lipoprotein expression is also relevant here, since the lpp gene product is a structural component of the cell envelope.…”
Section: Discussionsupporting
confidence: 68%
“…Although we could not clarify its mechanism of action, aurodox inhibited the secretion of some LEE-encoded proteins (EspA, EspB, EspD, EspF and Map) and EspC, a member of the immunoglobulin A protease family of autotransporters (Figure 3). It is known that the expression of LEE-encoded proteins and EspC is coordinately regulated by an LEE-encoded regulator, Ler, 28 and a BipA regulator, 29 a member of the ribosome binding GTPase family. Such findings suggest that aurodox inhibits the expression of genes under the control of Ler and/or BipA.…”
Section: Discussionmentioning
confidence: 99%
“…BipA has been shown to function as a master regulator by transcriptselective translational control (88). In E. coli, it is a master regulator of growth at low temperatures (91) and of the expression of genes in pathogenicity islands (43). Considering the conservation of domain arrangement and the 71% amino acid sequence identity between E. coli and P. putida BipA, we concluded that in P. putida BipA has a key role in adaptation to cold stress and growth at 4°C due to transcript-selective translation control.…”
Section: Indicated By Rt/pcr)mentioning
confidence: 99%